Internet Activist, a Creator of RSS, Is Dead at 26, Apparently a Suicide. - SCHWARTZ, JOHN (New York Times, 2013)
The article reports that 26-year-old computer software programmer and Internet activist Aaron Swartz was believed to commit suicide by his uncle, Michael Wolf, after he was found dead inside his apartment in New York City on January 11, 2013.